Myanmar’s Digital Learning Journey Through Distance Education - Nu Nu Yi; Thi Thi Khine (SEAMEO SEAMOLEC, 2024)
Myanmar, a nation renowned for its cultural diversity and natural beauty, grapples with enduring educational challenges that arise due to limited accessibility to quality education, insufficient infrastructure and a shortage of wellqualified teachers with adequate training. However, the advent of digital technologies and the transformative potential of distance education offer a hopeful path.This pioneering initiative aims to enhance Myanmar’s education system through digital distance learning. Its primary goal is to address long-standing educational disparities using technology for inclusive learning, including the development of digital infrastructure, and providing teacher training in digital pedagogy. Furthermore, partnerships with international organizations contribute expertise, resources, and innovation to distance education.Ultimately, Myanmar’s digital learning journey visualizes an inclusive and equitable education system with the potential for a brighter future built on digital skills and knowledge in order to enhance learning opportunities as well as eliminate knowledge disparities throughout the country